The influence of company size, profitability, solvency, and audit opinion on audit delay in Coal Mining Companies listed on the Indonesia Stock Exchange for the years 2018-2021 - Tampubolon, Pedro Samuel Bonatua; Purba, Olo Hasian S.; Pane, Afrizar; Harahap, Riva Ubar (Priviet Social Sciences Journal, 2024)
This study aims to investigate the effects of Company Size, Profitability, Solvency, and Audit Opinion on Audit Delay among coal mining companies listed on the Indonesia Stock Exchange from 2018 to 2021. The purposive sampling technique was employed, selecting from specific criteria to yield 40 samples. Secondary data on financial reports from the Indonesia Stock Exchange for the specified period were analyzed using linear regression with SPSS software. The data analysis methods included descriptive statistics, classical assumption tests, and multiple and simultaneous F regression analyses. The findings indicate that Company Size has a significant impact on Audit Delay, as evidenced by a t-value significantly higher than the t-table value. Profitability negatively and significantly affects Audit Delay, with a t-value also exceeding the t-table value. However, Solvency and Audit Opinion were found not to have a significant effect on Audit Delay, as their t-values did not surpass the critical t-table values.